ANALYSIS OF MEFENAMIC ACID LEVEL IN HERBAL MEDICINE FOR SCIATICA PAIN (AIR MANCUR) BY UV-VIS SPECTROPHOTOMETRIC METHOD - Baiq Husnul Hotimah Septiandi; Eva Larassati; Nabila Ramadhani; Abd Sukri S Manusu (DAS Institute, 2023)
Herbal medicine is a traditional medicine that is still popular today among the public. Herbal medicine for pain and rheumatism is one type of herbal medicine that is in great demand by consumers. Herbs are often added with medicinal chemicals to provide a faster and more effective effect so that it can attract consumers to use these herbal products, but basically the use of medicinal chemicals in herbal medicine is a dangerous thing because the dose contained in the herbal medicine is unknown but still used for a long time. The method used is the UV-Vis spectrophotometric method with a wavelength range of 200-400 nm. The research began with the collection of herbal medicine samples taken randomly in one of the shops in the city of Yogyakarta, the samples used were herbal medicine for sciatica pain produced by air mancur, then wavelength readings were taken, mefenamic acid standard solution analysis, and method validation. The method validation results obtained are the correlation value (R2) of 0.9998, the LOD value of 0, 073343 and LOQ 0.244476 ppm. This value exceeds the LOD and LOQ values so that it can be interpreted that the herbal medicine sample has a mefamic acid content of 4.643 ppm or 1.266%.